SPECIES COMPOSITION AND DIVERSITY OF TIDAL TRAP NET CATCHES IN THE WATERS OF INDRAGIRI HILIR, RIAU, INDONESIA - Badrudin Badrudin; Bambang Sumiono; T.S Murtoyo (Indonesian Fisheries Research Journal, 2001)
The coastal waters of the eastern part of lndragiri Hilir, Riau, which are mostly estuarine, are influenced by the huge fresh water discharge and are usually fertile.